For a dialectic of planning pasts and futures: Theoretical courses and recourses in conversation with Patsy Healey - Simone Tulumello (PlaNext)
Planning theory has done much, during the last decade or so, to broaden and enrich its own geographies: thanks to the engagements with critical urban studies and post-colonial theory, planning theorists have problematised the disciplinary insistence on certain modernist ideas and universalist approaches. Much less has been done to problematise the relation of planning with time—its ontology of action. This short essay takes step from my personal experience of editing a special issue of plaNext with Patsy Healey to argue for a different—dialectic, open, experimental—engagement of planning theory/practice with time, an endeavour that seems perfectly fit for a journal like plaNext turning 10 years old.